Hubungan Diet Dengan Kejadian Menstrual Sindrome (PMS) pada Remaja Putri di Pesantren Kota Kediri - Endah Luqmanasari; Naning Ayu Kalimantari (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
A high intake of fats, carbohydrates, sodium, and low calcium will increase the risk of PMS. The purpose of the research is to know if there is a diet correlation with PMS incidents in young women in Pesantren Kedunglo Kediri City. This study included a non-experimental observation without treatment. The design used is cross-sectional. Independent variables diet and the dependent variable incidence of PMS. The population in the study were young women in boarding schools in Kedunglo Kediri city 109 population, sampling techniques simple random sample of 85 respondents obtained. Research conducted on 5-14 August 2021. The instrument for data collection was a questionnaire sheet. This study uses statistical tests rank correlation test (Spearman). The results of the study most of the 54 respondents (64%) diet, got nearly half of the 34 respondents (40%) did not have PMS, while nearly half of 30 respondents (35%) do unhealthy diets obtaining a fraction of 19 respondents have PMS and a fraction 1 respondent (1%) healthy diet 1 respondent obtained fraction (1%) did not have PMS. Statistical analysis showed that the Spearman rank correlation test values ​​obtained ρvalue = 0.000 <α 0,05 means rejected accepted by value (Correlation coefficient = 0.041) means that the strength of correlation between two variables (diet meal on the incident of PMS) included in the criteria of a low level of correlation there is correlation diet with PMS incident in young girls at boarding schools Kedunglo Kediri city.PMS by physical and emotional symptoms that consistently occur during the luteal phase of the menstrual cycle symptoms due to hormonal changes that occur in a woman's body before menstrual.